Pengaruh Penggunaan Media Pembelajaran Flipchart terhadap Hasil Belajar Kognitif Siswa Kelas X SMA Negeri 24 Maluku Tengah : (The Effect of Using Flipchart Learning Media on Cognitive Learning Outcomes of Class X Students of SMA Negeri 24 Maluku Tengah) - Calvin Talakua; Febiayu Aloatuan (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
The accuracy of using the media indirectly will stimulate students to take part in these lessons so that it will affect the good and bad results of student learning. The research design used Two Group Randomized Subjeck Posttest Only, by selecting two classes, namely the experimental class group and the control class group. The experimental class group used Flipchart learning media while the control class used conventional learning models. The same test was given to both classes, namely at the end of the lesson (posttest). From the results obtained, it is known that the cognitive learning outcomes of students using flipchart learning media are much better than students who use conventional learning models. This can be seen from the average score of the experimental class which is much higher than the control class, which is 80.44, while the control class is 58.93. From the results of hypothesis testing, it shows that tcount = 4.26 and ttable = 1.67 at the significant level α = 0.05 with degrees of freedom dk = (34+ 34-2). Based on the criteria for the hypothesis accept H0 if tcount <ttable with degrees of freedom dk = (n_1 + n_ (2) - 2) with a significant level α = 5% for other t values ​​H0 is rejected. Judging from the results of the calculation, it is known that the value of tcount> ttable. So that H_ (0) is rejected and H1 is accepted, which means that there is an effect of Flipchart learning media on cognitive learning outcomes of class X students of SMA Negeri 24 Maluku Tengah. Abstrak. Ketepatan penggunaan media secara tidak langsung akan menimbulkan rangsangan dari diri siswa untuk mengikuti pelajaran tersebut sehingga akan mempengaruhi baik buruknya hasil belajar siswa. Desain penelitian ini menggunakan Two Group Randomized Subjeck Posttest Only, dengan memilih dua kelas yaitu kelompok kelas eksperimen dan kelompok kelas kontrol. Kelompok kelas eksperimen menggunakan media pembelajaran Flipchart sedangkan kelas kontrol menggunakan model pembelajaran konvensional. Tes yang sama diberikan pada kedua kelas yaitu pada akhir pembelajaran ( postes). Dari hasil yang didapat diketahui hasil belajar kognitif siswa yang menggunakan media pembelajaran Flipchart jauh lebih baik daripada siswa yang menggunakan model pembelajaran konvensional. Hal ini dilihat dari rata-rata skor kelas eksperimen yang jauh lebih tinggi dari kelas kontrol yaitu 80.44 sedangkan kelas kontrol 58,93. Dari hasil pengujian hipotesis menunjukan bahwa thitung = 4.26 ttabel = 1.67 pada taraf singnifikan = 0,05 dengan derajat kebebasan dk = (34+ 34 - 2 ). Berdasarkan kriteria hipotesis terima H0 jika thitung < ttabel dengan derajat kebebasan dk = ( + - 2 ) dengan taraf signifikan = 5% untuk nilai t lainnya H0 ditolak. Dilihat dari hasil perhitungan yang didapat diketahui nilai thitung ttabel Sehingga demikian ditolak dan H1 diterima yang artinya bahwa ada pengaruh media pembelajaran Flipchart terhadap hasil belajar kognitif siswa kleas X SMA Negeri 24 Maluku Tengah.